2009
DOI: 10.1007/s00330-009-1633-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of lung development in isolated congenital diaphragmatic hernia using signal intensity ratios on fetal MR imaging

Abstract: Changes in LLSIR seem to reflect developmental impairment in CDH; however, they provide no additional information in predicting outcome. LV remains the best indicator on fetal MR imaging of neonatal survival in isolated, left-sided CDH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 47 publications
2
31
0
Order By: Relevance
“…It has also been used to predict the need for extracorporeal membrane oxygenation [35,36] . Recently, the group of Prayer demonstrated that lung signal intensity ratios did not have any additional value in predicting prognosis [37] . MRI can also demonstrate the presence of liver herniation.…”
Section: Imaging Anatomical Parameters As Prognostic Predictors In Cdhmentioning
confidence: 99%
“…It has also been used to predict the need for extracorporeal membrane oxygenation [35,36] . Recently, the group of Prayer demonstrated that lung signal intensity ratios did not have any additional value in predicting prognosis [37] . MRI can also demonstrate the presence of liver herniation.…”
Section: Imaging Anatomical Parameters As Prognostic Predictors In Cdhmentioning
confidence: 99%
“…22,23 Although the pathogenesis of pulmonary hypoplasia in CDH remains poorly understood, the fetal lung fluid has a key role in normal lung development as is mentioned. 24,25 Recent studies using MRI signal intensity for fetuses with CDH showed both positive 26 and negative 27,28 data for prediction of survival prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Lung volumes increase significantly with time, but longterm follow-up studies in children with surgical repair of congenital diaphragmatic hernias have shown persistent reduced lung perfusion in the lung ipsilateral to the hernia compared to the contralateral lung [43]. Recently, Balassy et al [44] assessed development of both lungs in patients with isolated congenital diaphragmatic hernia by using lung/liver signal intensity ratios on T1-and T2-W images. They found that lung/liver signal intensity ratios were significantly higher in both lungs on T1-W and significantly lower on T2-W images compared with normal lungs and concluded that although these changes seem to reflect developmental impairment in both lungs, they provide no additional information in predicting final outcome.…”
Section: Prenatal Diagnosis Of Congenital Diaphragmatic Defectsmentioning
confidence: 99%